2001
DOI: 10.1002/rem.1025
|View full text |Cite
|
Sign up to set email alerts
|

The hyporheic zone: Linking groundwater and surface water—understanding the paradigm

Abstract: The hyporheic zone, the transition region between groundwater and surface water, represents an important interface between terrestrial and aquatic ecosystems. When groundwater combines with surface water in this zone, the characteristics of each are blended and new gradients are established, especially for contaminants. Therefore, the hyporheic zone is important in considering the “big ecological picture” as the hydrologic continuum connecting groundwater and surface water. The importance is reflected by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…The lateral hyporheic area has been observed to vary by as much as 50% during the course of a year in a semiarid environment (Wroblicky et al, 1998). This zone is very dynamic (Biksey and Gross, 2001) and can also be a contaminant sink (Fuller and Harvey, 2000; Winde and van der Walt, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The lateral hyporheic area has been observed to vary by as much as 50% during the course of a year in a semiarid environment (Wroblicky et al, 1998). This zone is very dynamic (Biksey and Gross, 2001) and can also be a contaminant sink (Fuller and Harvey, 2000; Winde and van der Walt, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Infiltrated stream water contribution to site water balance was calculated using Guelf permeameter-derived saturated hydraulic conductivity (k sat D 2Ð5 cm day 1 ), average potential gradient between stream and groundwater (head/distance: 0Ð085; see Figure 9) and Darcy's equation for saturated flow. Small-diameter piezometers are frequently used to measure the hydraulic gradient between surface water and groundwater (Biksey and Gross, 2001) and allow for the determination of directional water flux. This measurement was used to verify the accuracy of the site water balance estimation of hyporheic input.…”
Section: Propagation Of Errors and Independent Measurement Of Hyporhementioning
confidence: 99%
“…The hydro-biogeochemistry controls the cycling of nutrients, such as carbon, nitrogen, and phosphate, the migration and propagation of pathogens, and the transformation and attenuation of heavy metals and contaminants (Boulton et al, 1998;Herzog et al, 2016;Siergieiev et al, 2014). The HZ biogeochemical functions such as attenuating and removing contaminants have been increasingly recognized in the research community (e.g., Biksey & Gross, 2001;Gandy et al, 2007;Herzog et al, 2016;Lawrence et al, 2013;Palumbo-Roe et al, 2017). Landmeyer et al (2010) found that several fuel oxygenates (methyl tert-butyl ether, tert-butyl alcohol, and tert-amyl methyl ether) in GW were attenuated by 71% on average along a 1.5-m vertical interval of the HZ.…”
Section: Introductionmentioning
confidence: 99%